IMPORTANCE OF STRATEGIC INFORMATIONS FOR PLANNING IN BASKETBALL - Pavle Rubin; Predrag Peruško (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Planning in basketball (like in other sports) is one aspect of the job of a sport coach. Every coach while writting (creating, composing) the plan and programme of a trainning (trainning proces) should have the informations important for achievingsuccess. That kontigent of informations should be hierarchy arranged. Driving the pro- gramme the coach should always barring in mind what is the most important aim which in particular moment he wants to realise. Problem of this work is in fact that difference between coaches is that thay dont give certain importance to the particular informati- ons. Beside the necessity to know wich informations are the most important for solving a problem, it is important to prove their corelations. The aim of the research is to present the importance of identification and using of strategic infomations in planning (and pro- gramming) in basketball. According to all infomations colected by coach he creates his strategic koncept. Using the strategic koncept he can create tactical koncept, particular koncept for the particular opponent (tactical plan) and to (more or less) use intime cer- tain tactical variance on the game (operative tactics). The coach (as the most important in the trainning process) should be familiar with the science aspects of sport activities. That way he can overtake expected integral functions and be a lieder who gain the aim.